2022
DOI: 10.3389/fimmu.2022.852300
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vaccination With Recombinant Pichia pastoris Expressing Iridovirus Major Capsid Protein Elicits Protective Immunity in Largemouth Bass (Micropterus salmoides)

Abstract: Largemouth bass iridovirus (LMBV) can cause high mortality and lead to heavy economic loss in the cultivation of largemouth bass, but there was no effective treatment. Here, the present study constructed a recombinant Pichia pastoris expressing LMBV major capsid protein (MCPD). The recombinant GS115-pW317-MCPD was then used to immunize largemouth bass via oral administration, and mucosal immune response mediated by immunoglobulins (Igs) was measured after oral immunization. Serum antibody levels were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In this work, transcription levels of both immunoglobulin IgM heavy chain ( IgMH ) and immunoglobulin T heavy chain (IgTH) in the head kidney, spleen, skin, and gill tissues of rCiSA32.6t-immunized L. crocea were significantly higher than those of control group. A similar phenomenon has been reported in largemouth bass ( Micropterus salmoides ) vaccinated with recombinant major capsid protein (rvp7) of Largemouth bass iridovirus (LMBV) (Yao et al 2022 ). The results were also in accordance with the expression level of serum IgM and IgT antibody, which clearly suggested that L. crocea could be stimulated to produce a high-titer specific antibody by rCiSA32.6t and acquired better immune protection.…”
Section: Discussionsupporting
confidence: 70%
“…In this work, transcription levels of both immunoglobulin IgM heavy chain ( IgMH ) and immunoglobulin T heavy chain (IgTH) in the head kidney, spleen, skin, and gill tissues of rCiSA32.6t-immunized L. crocea were significantly higher than those of control group. A similar phenomenon has been reported in largemouth bass ( Micropterus salmoides ) vaccinated with recombinant major capsid protein (rvp7) of Largemouth bass iridovirus (LMBV) (Yao et al 2022 ). The results were also in accordance with the expression level of serum IgM and IgT antibody, which clearly suggested that L. crocea could be stimulated to produce a high-titer specific antibody by rCiSA32.6t and acquired better immune protection.…”
Section: Discussionsupporting
confidence: 70%
“…Neutralizing antibody plays a critical role in defending organisms against pathogens [ 23 , 24 ]. It was reported that oral delivery of recombinant S. cerevisiae cells could be engulfed by the intestinal epithelial cells of gut in crucian carp, and heterologous protein-specific antibodies could be detected in the serum of vaccinated fish [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration is an ideal immunization route for fish at all life stages, especially the juvenile stage [ 10 , 27 ]. Displaying antigenic proteins on the surface of S. cerevisiae cells is a promising approach for the development of oral vaccines [ 24 ]. In this study, oral administration of EBY100/pYD1-ORF132 gave a 64% RPS in CyHV-2-infected crucian carp.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is considered an ideal approach for preventing LMBV infection. Although some candidate vaccines and herbal extracts have been proven to be potent for defending against LMBV infection under laboratory conditions, there is no licensed vaccine or antiviral drug available for preventing or treating LMBV infection (Jia et al, 2022;Yao et al, 2022;Cheng et al, 2023;Wang et al, 2023;Zhang, M. et al, 2023). Therefore, rapid detection and early diagnosis of LMBV remain crucial strategies to prevent the disease's spread and mitigate economic loss.…”
Section: Introductionmentioning
confidence: 99%